2001
DOI: 10.1038/414660a
|View full text |Cite
|
Sign up to set email alerts
|

AID is required to initiate Nbs1/γ-H2AX focus formation and mutations at sites of class switching

Abstract: Class switch recombination (CSR) is a region-specific DNA recombination reaction that replaces one immunoglobulin heavy-chain constant region (CH) gene with another. This enables a single variable (V) region gene to be used in conjunction with different downstream CH genes, each having a unique biological activity. The molecular mechanisms that mediate CSR have not been defined, but activation-induced cytidine deaminase (AID), a putative RNA-editing enzyme, is required for this reaction 1 . Here we report that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
438
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 462 publications
(470 citation statements)
references
References 30 publications
29
438
0
3
Order By: Relevance
“…The DNA damage signaling kinases, ataxia telangectasia mutated (ATM), ATM-and Rad3-related protein (ATR) and DNA-dependent protein kinase catalytic subunit (DNA-Pkcs) were found to be responsible for the generation of g-H2A.X [Burma et al, 2001;Stiff et al, 2004]. H2A.X phosphorylation appears at sites of DSBs during DSB repair, meiotic recombination [Hunter et al, 2001;Mahadevaiah et al, 2001], apoptotic digestion , V (D) J splicing [Chen et al, 2000;Gellert, 2002], and class switch recombination [Petersen et al, 2001]. It therefore seems to be a universal cellular response to DSBs.…”
Section: Histone H2a Variantsmentioning
confidence: 99%
“…The DNA damage signaling kinases, ataxia telangectasia mutated (ATM), ATM-and Rad3-related protein (ATR) and DNA-dependent protein kinase catalytic subunit (DNA-Pkcs) were found to be responsible for the generation of g-H2A.X [Burma et al, 2001;Stiff et al, 2004]. H2A.X phosphorylation appears at sites of DSBs during DSB repair, meiotic recombination [Hunter et al, 2001;Mahadevaiah et al, 2001], apoptotic digestion , V (D) J splicing [Chen et al, 2000;Gellert, 2002], and class switch recombination [Petersen et al, 2001]. It therefore seems to be a universal cellular response to DSBs.…”
Section: Histone H2a Variantsmentioning
confidence: 99%
“…These foci are essential in facilitating the assembly of repair factors, including Brca1 and the MRE11-RAD50-NBS1 complex, on damaged DNA (Paull et al, 2000;Celeste et al, 2002), and also aid in the transduction of DNA damage signals by binding to 53BP1 and MDC1 (FernandezCapetillo et al, 2002;Stewart et al, 2003). gH2AX foci also form at sites of physiological DSBs in lymphocytes and germ cells (Chen et al, 2000;Mahadevaiah et al, 2001;Petersen et al, 2001;Fernandez-Capetillo et al, 2003). Knocking out H2AX produces mice with immune deficiency and male infertility , while loss or reduction of H2AX compromises genome stability and facilitates tumorigenesis Bassing et al, 2003;Celeste et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…As eluded to in the introduction, experimental evidence has demonstrated that CSR, like V(D)J recombination, involves the generation of DNA dsb: (1) an episomal circle is generated during CSR (Chaudhuri and Alt, 2004); (2) AID-dependent DNA dsb have been detected by ligated mediated PCR assays in Switch regions of mitogen-activated B cells (Wuerffel et al, 1997;Catalan et al, 2003;Rush et al, 2004); (3) phosphorylation of histone H2AX (gH2AX), which spreads around DNA dsb, is detected at the IgH locus in an AID-dependent manner, in B cells activated for CSR (Petersen et al, 2001); (4) CSR is impaired in mice deficient for H2AX, ATM, p53 binding protein 1 and Nbs1, which are DDR early components (Reina-San-Martin et al, 2003, 2004Lumsden et al, 2004;Manis et al, 2004;Ward et al, 2004;Kracker et al, 2005). The link between AIDdriven DNA cytidine deamination and the introduction of DNA dsb in Ig S regions is not fully established yet.…”
Section: Nhej and Csrmentioning
confidence: 99%